“Modelo de Gestión Administrativa y Financiera, para La Cooperativa de Transportes “Rio San Pablo” del cantón La Maná, Provincia de Cotopaxi. - Arévalo Noboa, Ligia Elena (2020)
One of the main premises of an administrative and financial management model is to link the company with its environment and establish the objectives, developing integration plans, allowing a correct allocation of resources through defined procedures and means for measuring their results. The Río San Pablo transportation cooperative in La Maná canton, characterized by informal administrative management, with low levels of strategic and financial planning. Because of the cooperative detected a low level of control in the schedules and disorganization in the administrative and financial part, it was considered essential to develop a model of administrative and financial management, for the transportation cooperative "Rio San Pablo" in La Maná, Cotopaxi province, through a foundation of the theoretical elements with a bibliographical investigation. In order to fulfill the objectives established in the research, exploratory, descriptive, bibliographic research and inductive and analytical research methods were used. The situational diagnosis through the interview with the manager and surveys of the partners could be known that in the entity the institutional mission and vision is not available in a documented way, an organizational structure, outdated, it could also be evidenced that the administrative activities are carried out manually without receiving any specialized advice and the functions performed are the product of the experience acquired over the years as a member of this cooperative. The administrative management model for the Río San Pablo Transportation Cooperative began with a detail of the generalities of the cooperative, and the administrative components were focused on the planning processes with the approach of the mission, vision, values and SWOT analysis, the organization process, by the structural organization chart, functions manual by areas, map and process sheet; the address through the evaluation test and a check list for the transport units. While the components of the financial management model were the financial area functions manual, horizontal and vertical analysis, scenarios and financial indicators.